Characterization of multi-wavelength polarized light transmission in the real sea spray environment - Luo, Kaiming; Fu, Qiang; Zhang, Yue; Yang, Wei; Zhang, Su; Zhan, Juntong; Li, Zheng; Ma, Yi; Duan, Jin; Jiang, Huilin (Frontiers in Physics, 2023)
Sea spray particles are a kind of non-uniform, non-spherical, non-isotropic and complex medium, and the study of the transmission characteristics of polarized light in a real sea spray environment can provide reference value in many fields such as polarization imaging, marine target detection, and LIDAR, which can make up for the vacancy of polarized light transmission in a complex sea spray environment. In this paper, a real sea fog test is carried out in Qingdao sea area of China in the horizontal/oblique direction, and a platform for generating and detecting polarized light with multiple tilt angles is constructed by using the active test method, which realizes the test scheme for the characteristics of energy change and polarization state change of linearly polarized light and circularly polarized light under different visibility sea fog environments. The results show that it is more difficult to deflect circularly polarized light than linearly polarized light under the same sea spray visibility. With the increase of the tilt angle, the polarization are decreasing. The polarization of near-infrared light is always larger than that of visible light, which indicates that the circularly polarized light has better polarization preservation than linearly polarized light and the polarization preservation of near-infrared light is better than that of visible light.